Room-Temperature Synthesis of the TiC, ZrC, HfC, VC, NbC and TaC Powder Monocarbides - Nakonechna, Olesya; Belyavina, Nadezhda; Dashevskyi, Mykola; Titov, Yuri Alexandrovich (Київський національний університет імені Тараса Шевченка, 2019)
The nanoscaled (up to 30 nm) TiC, ZrC, HfC, VC, NbC and TaC monocarbides with NaCl-type structure have been synthesized from the elemental metals and the carbon nanotubes (CNTs) by mechanical alloying in a high energy planetary ball mill in an argon atmosphere. The powders obtained were examined by X-ray diffraction method. It is shown that mechanical alloying is accompanied by a decrease in the lattice parameters of MeC carbides formed and by a decrease of the total number of atoms in their crystal structure, i.e. by an increase of structural vacancies in the materials obtained. On the whole, monocarbides obtained can be arranged by the simplicity of their formation in a ball mill as: HfC -> ZrC -> TiC -> TaC -> NbC -> VC.
Keywords: nanocomposite; carbide; mechanical alloying; X-ray diffraction; crystal structure